Beyond market dystopia : new ways of living - Panitch, Leo; Albo, Gregory (Socialist register (London, England) ;, 2019)
How can we build a future with better health and homes, respecting people and the environment? The 2020 edition of the Socialist Register, Beyond Market Dystopia, contains a wealth of incisive essays that entice readers to do just that: to wake up to the cynical, implicitly market-driven concept of human society we have come to accept as everyday reality. Intellectuals and activists such as Michelle Chen, Nancy Fraser, and Roger Keil connect with and go beyond classical socialist themes, to combine an analysis of how we are living now with visions and plans for new strategic, programmatic, manifesto-oriented alternative ways of living. Crafted with purposeful hope in an age of despair, each essay in this volume aims to create a world of agency and justice.